Case Report: Ileo-Ileal Intussusception Secondary to Inflammatory Fibroid Polyp: A Rare Cause of Intestinal Obstruction - Guerci, Claudio; Colombo, Francesco; Goi, Gloria; Zerbi, Pietro; Pirrò, Barbara; Danelli, Piergiorgio (Frontiers in Surgery, 2022)
Introduction Intussusception is a telescoping of a bowel segment into another and it can be a surgical urgency. Most adult intussusceptions arise from a lead point which can be a benign or malignant lesion. For this reason, intussusception in adults should undergo surgery. Here we present a rare case of ileal inflammatory fibroid polyp (IFP), presenting with ileo-ileal intussusception and obstruction. Case description An adult woman presented for acute abdominal pain, with minimal abdominal distension and tenderness. A plain radiography and a CT of the abdomen were performed, which showed typical signs of occlusion due to an ileo-ileal intussusception. An urgent laparoscopy was performed, the intussusception was extracorporeally reduced, the ileal segment involved was resected, and an ileo-ileal anastomosis was performed. The intussusception seemed to be caused by a 3-centimetres intra-mural lesion. Discussion Intussusception is a surgical concern which usually occurs with acute abdomen signs. While the majority of cases are idiopathic in children, 90% of adult intussusceptions are caused by underlying diseases, which can be benign or malignant. Therefore, intussusception in adults should undergo surgery. Radiology is necessary for the diagnosis: the CT scan helps localizing the lesion and shows pathognomonic signs. This case report analyzes an intussusception caused by an inflammatory fibroid polyp. Accurate diagnosis of IFP is only possible with histopathological examination, helped by the immunohistochemical profile, which can vary amongst the IFPs. The differential diagnosis is important, because some lesions are malignant, like GISTs and lymphomas, some others could be recurrent, like IMTs. Conclusions We reported a case of intussusception caused by an inflammatory fibroid polyp in an adult woman. The diagnosis was made with a CT scan together with intraoperative findings and histopathological examination, which excluded potential differential diagnoses. The patient underwent an explorative laparoscopy, with an ileal resection and anastomosis. Due to the risk of malignancy, surgery is mandatory.